CREATING AN INTERACTIVE LEARNING ENVIRONMENT THROUGH ARTIFICIAL INTELLIGENCE IN MOBILE APPLICATIONS (Universal International Scientific Journal, 2026)
In the current era of globalization, the importance, opportunities and prospects of creating an interactive and modern educational environment using artificial intelligence (AI) technologies based on mobile applications are considered. Unlike traditional educational methods, the issues of organizing a personalized learning process, increasing the effectiveness of learning, and maintaining user motivation through artificial intelligence are analyzed.
Keywords: : Mobile learning (m-learning), artificial intelligence (AI), interactive learning environment, personalized learning (personalization), adaptive learning.